Pet Bottle Recycling at PT. Calista Prima Piranti Indah - Adrian Gabriel Hanesto Napitupulu; Rustina Untari (Soegijapranata Catholic University, 2024)
The discovery of plastic as a material that is useful for human life, providing comfort and convenience has now turned into a threat to society and suffering because plastic has also become a habitat with the human ecosystem. Plastic is made by humans, but plastic can live far longer than humans which gives them the privilege of living. Because this material cannot be destroyed by itself, it is very important to find possible ways to destroy, or even reuse, plastic bottle waste. Steps that can be taken are recycling by turning plastic bottle waste into raw materials that are useful for other sectors of the economy. This paper shows the fact that it is important to recycling plastic waste, especially plastic bottles, and the party that is motivated to recycle plastic bottles into bottles that can be reused, namely PT. Calista Prima Piranti Indah is located in Semarang City, Central Java, Indonesia.